2012
DOI: 10.1210/jc.2011-1944
|View full text |Cite
|
Sign up to set email alerts
|

Positive Impact of Long-Term Antithyroid Drug Treatment on the Outcome of Children with Graves' Disease: National Long-Term Cohort Study

Abstract: About half the patients achieved remission after carbimazole discontinuation, and there seems to be a plateau in the incidence of remission achieved after 8-10 yr ATD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
139
5
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 39 publications
9
139
5
10
Order By: Relevance
“…There is some controversy on the use of MMI as a first-line treatment of pediatric hyperthyroidism and we used, similar to other studies, methimazole as the first-line therapy in all patients [19,20,[22][23][24][25]. Remission rates after ATD withdrawal varied in different studies ranging from 33% to 64% [6,23,26].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…There is some controversy on the use of MMI as a first-line treatment of pediatric hyperthyroidism and we used, similar to other studies, methimazole as the first-line therapy in all patients [19,20,[22][23][24][25]. Remission rates after ATD withdrawal varied in different studies ranging from 33% to 64% [6,23,26].…”
Section: Discussionmentioning
confidence: 90%
“…Another prospective study showed that relapse risk of hyperthyroidism decreased with the duration of the first course of ATD and every additional year of ATD therapy was associated with a decrease in the relapse rate [20]. Another study evaluated the effect of the duration of ATD treatment after three consecutive courses, each lasting for 2 years and found a remission rate of 50% after discontinuation of ATD treatment [24]. We did not study the relapse rate of hyperthyroidism following discontinuation of long-term ATD treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Максимальные сроки лечения тиреостатиками у детей и подростков не определены, но большин-ство авторов склоняются к 12-18 мес, мак-симум 2 года. В случае развития осложне-ний отсутствие эффекта на фоне лечения и рецидив тиреотоксикоза являются показа-ниями для смены тактики лечения с выбо-ром радио йодтерапии (РЙТ) или тиреоид-эктомии [1,10]. Отсутствие значительного снижения уровня антител к рецептору тирео-тропного гормона после РЙТ, высокий уро-вень тиреоидных гормонов в крови, размер ЩЖ более 80 мл, а также наличие тиреоток-сикоза более чем через 3 мес после РЙТ явля ются предикторами неэффективности РЙТ [6,10,11].…”
Section: ключевые слова: радиойодтерапия дети подростки болезнь грunclassified
“…Data from Europe and North America have shown that short-term side effects such as thyroid storm are uncommon following RI administration in patients with thyrotoxicosis and the low additional radiation exposure during therapy has not resulted in a measurable overall increase in long-term neoplasia, or other adverse effects, to date (1,2). This information is of considerable potential value to paediatric endocrinologists because a 2-to 4-year course of anti-thyroid drugs will only result in remission in a minority of patients (2,3). Although anecdotal evidence suggests that some paediatric endocrinologists in the UK now consider RI to be a safe and effective alternative to surgery in young patients with thyrotoxicosis, there is as yet no formal strategy in Great Britain to collect longerterm data on RI usage in the young or to study any potential long-term consequences of these exposures on health.…”
Section: Introductionmentioning
confidence: 99%